MECHANISMS OF ARTERIAL AND VENOUS HYPEREMIA - Umurov Erkin Utkirovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Arterial and venous hyperemia represent two distinct forms of increased blood flow to tissues, each with different underlying mechanisms and physiological implications. Arterial hyperemia refers to an increase in blood flow due to vasodilation of arterioles, while venous hyperemia is caused by impaired venous return and venous congestion. Both forms of hyperemia are important in understanding various cardiovascular conditions, including inflammation, ischemia, and organ perfusion. This article explores the mechanisms behind arterial and venous hyperemia and their clinical relevance.